Selection for contrasting adrenocortical responsiveness in Japanese quail (Coturnix japonica) influences sexual behaviour in males - Marin, Raul Hector (2003)
Selection of Japanese quail for a reduced (low stress, LS) rather than exaggerated (high stress, HS) adrenocortical response to brief restraint is associated with a non-specific reduction in stress responsiveness, decreased fearfulness, greater sociality, and enhanced male reproductive function, e.g. greater cloacal gland size, foam production, and testes weight. Because sexual behaviour has components that may be affected by all of these traits, the copulatory behaviour of male LS and HS adults was compared herein. In experiment 1, males from each line were individually tested in a runway (novel environment) in two consecutive steps. First, the approach (social proximity) of a test male (LS or HS) to a compartment containing two females (one LS+one HS) that he could see but not reach was examined. Second, after allowing the test male and both females to mingle, the male's latency to first grab and the numbers of grabs, mounts and cloacal contacts were recorded. A tendency for LS males to spend a longer (P = 0.08) amount of time near the females before the sexes were mingled was observed. When the birds were allowed contact, LS males showed a significantly higher (P < 0.04) number of cloacal contacts and greater (P < 0.04) copulatory efficiency (number of cloacal contacts/number of grabs) than HS males. No line differences were observed in the latency to the first grab, grabs, and mounts. In experiment 2, individually-caged males from each line were observed when one female (LS or HS) was introduced into their home cages as a sexual partner. The LS males showed a lower latency to the first grab and greater cloacal contacts and copulatory efficiency than HS quail (all P < 0.03). The present findings suggest that quail selection for reduced adrenocortical stress responsiveness prior to the attainment of puberty has a positive impact on adult sexual behaviour of males. © 2003 Elsevier B.V. All rights reserved.